Current Population Survey, May 2010 - May 2011: Tobacco Use Supplement (TUS), 2010 - 2011 Wave ([Verlag nicht ermittelbar], 2016)
This data collection is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a Tobacco Use Supplement (TUS) survey sponsored by The National Cancer Institute (NCI). The TUS 2010-2011 Wave consists of four collections: May 2010, August 2010, January 2011, and May 2010-May 2011. The Current Population Survey, administered monthly, is the source of the official government statistics on employment and unemployment. From time to time, additional questions are included on health, education, and previous work experience. Similar to other CPS supplements, the Tobacco Use Supplement was designed for both proxy and self-respondents. All CPS household members aged 18 and older who had completed CPS core items were eligible for the supplement items. Both proxy and self-respondents were asked about their smoking status and the use of other tobacco products. For self-respondents only, different questions were asked depending on their tobacco use status; for former/current smokers, questions were asked about type of cigarettes smoked, measures of addiction, attempts to quit smoking, methods and treatments used to quit, cost of cigarettes, age initiating everyday cigarette smoking and the state of residence at that time, etc. Current smokers were asked whether the medical and dental community had advised them to quit smoking, and if they were planning to quit in the future. All self-respondents were asked about smoking policy at their work place and their attitudes towards smoking in different locations. A unique feature of the CPS is its panel design, in which each household in the sample is surveyed for four consecutive months and nine months later for four more consecutive months. NCI took advantage of this panel design to follow-up with respondents from the May 2010 TUS by asking them similar questionnaire items in May 2011, resulting in a one year longitudinal cohort for half the May 2010 sample size. Demographic information within the study includes age, sex, race, Hispanic origin, marital status, veteran status, educational attainment, family relationship, occupation, and income.